Perfil lipídico da membrana citoplasmática de espermatozoides in natura e criopreservados de jumentos e cavalos - Chaves, Maria Manoela Barata de Castro [UNESP] (2015)
The horses and donkeys belong to the Equidae family and genus Equus, for this reason are considered similar and treated equivalently with respect to reproductive physiology. The plasma membrane of the sperm works as a physical barrier to the external environment and its structural integrity is directly related to the type and quantity of lipids that comprise it. Thus, this study aimed to compare the lipid profile of sperm donkeys and horses and compare the lipid membrane of the donkey sperm before and after cryopreservation processes. In Experiment 1 compared the lipid profile of the donkeys and horses sperm membrane and 101 lipid ions were identified in horses and 105 donkeys in. The donkeys had higher relative abundance in 18 ions. In Experiment 2 were evaluated changes in the lipid profile of the donkeys sperm membrane during the cryopreservation process and there was loss of 14 lipid ions and 16 new lipid ions arose after the cryopreservation processes. According to the obtained results we can conclude that the lipid composition of donkey sperm membrane is different from horses and cryopreservation processes lead to changes in the phospholipid composition of the plasma membrane of sperm donkeys